(3aJGhi Gdfhhj (B/s - (3Gdfhhj, jMji Hf TQa Hf eQjs 631-676 (3gLQjs; (3GHf GdYWGQ, Ydj Hf EHQGgje Hf OGhOs 654-724 (3gLQjs; (3GdCRgQj, eUWai eMehOs; (3Gdfhhj, jMji Hf TQa Hf eQjs 631-676 (3gLQjs ((3GdQjGV (B:s (3OGQ GHf Gdbje ddfTQ hGdJhRjY ,s (3GdbGgQI (B:s (3OGQ GHf YaGf ddfTQ hGdJhRjY,s, 2015)
(3gPG GdcJGH ehShYI abgjI eHSWI jLO ajg GdbGQF cd eG jMJGLg aj GdYHGOGJ hGdeYGedGJ HCSdhH Sgd ejSQ dG ZehV ajg hdG GVWQGH(B. (3hde jcJa GdEeGe aj cJGHg gPG HPcQ CbhGd GdYdeGA, hEfeG bGe HJQLjM eG jQGg QGLMG, hfbO GdCbhGd GdJj dG jQGgG JJWGHb hQhM GdTQjYI(B. (3hef GdeYQha Cf cJGH (B"(3aJGhi GdEeGe Gdfhhj(B" (3djS cd eG ajg ef faS GdcJGH, Hd Ef JdejPg GHf GdYWGQ Vefg HYV GdeSGFd GdCNQi hCLhHJgG eeG de jcf aj GdaJGhi(B. (3hWQjbI GHf GdYWGQ aj JQJjH (B"(3GdaJGhi(B" (3gj Gfg dh de jLO LhGH GdeSCdI aj GdcJGH hjQjO Cf jVja eeG cJHg aj GdeLdS, hjbhd aj BNQ GdLhGH (B"(3cJHg Yfg(B" (3hgPG Odjd Ydi Cf GdLhGH bO CVGag GHf GdYWGQ, hde jcf ehLhOG aj fU GdcJGH(B. s
(3cTGaGJ (B: (3UaMI (B283-292.s
(3HHdjhLQGajI (B: (3UaMI (B293-303.s
(3jTJed Ydj EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3Gdabg GdTGaYjs -- (3aJGhis